CANCER RISK IN MULTIPLE SCLEROSIS PATIENTS TAKING CLADRIBINE. Issue 10 (9th September 2014) - Pakpoor, Julia; Disanto, Giulio; Altmann, Daniel R; Pavitt, Sue; Turner, Benjamin; Calado-Marta, Monica; Juliusson, Gunnar; Baker, David; Chataway, Jeremy; Schmierer, Klaus
Abstract : Background: A large phase III trial (CLARITY) of oral cladribine (Movectro) in people with relapsing-remitting multiple sclerosis (pwRRMS) reported significant efficacy. However, a suspected cancer risk was key for the rejection of Movectro by the European Medicines Agency in 2010. We compared the cancer risk of Movectro with other disease-modifying therapies (DMTs). Methods: Phase III trials of approved DMTs for pwRRMS were identified. Fisher's exact test was used to compare cancer rates. Results: Twelve trials were included. Study heterogeneity was not significant. The CLARITY placebo group had a lower cancer rate (0%) compared to all other placebo groups (1.19%), p=0.0159. The cancer rate in the CLARITY treatment group (1.13%) was not increased compared to all other treatment groups (0.6%), p=0.1139. The CLARITY placebo group had a lower cancer rate compared to the recently completed trial of Movectro in people with clinically isolated syndrome suggestive of demyelination (ORACLE), p=0.0012. In contrast, no difference was detected between cancer rates in the treatment groups of CLARITY vs ORACLE (p=1). Conclusion: Movectro does not increase cancer risk in pwRRMS. Long term follow-up will help determine the cancer risk of all DMTs. Given its efficacy, tolerability and convenience cladribine should be reconsidered for treatment in pwRRMS.